2010
DOI: 10.1038/aja.2010.68
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and DNA damage in human spermatozoa

Abstract: DNA damage is frequently encountered in spermatozoa of subfertile males and is correlated with a range of adverse clinical outcomes including impaired fertilization, disrupted preimplantation embryonic development, increased rates of miscarriage and an enhanced risk of disease in the progeny. The etiology of DNA fragmentation in human spermatozoa is closely correlated with the appearance of oxidative base adducts and evidence of impaired spermiogenesis. We hypothesize that oxidative stress impedes spermiogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
191
1
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(207 citation statements)
references
References 78 publications
(83 reference statements)
7
191
1
8
Order By: Relevance
“…Several studies demonstrated the impact of sperm DNA damage and its correlation with clinical endpoints including fertilization rates, embryonic development, implantation, pregnancy and miscarriage rates [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated the impact of sperm DNA damage and its correlation with clinical endpoints including fertilization rates, embryonic development, implantation, pregnancy and miscarriage rates [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…2 ), hydrogen peroxide (H 2 O 2 ) and a highly toxic hydroxyl radical (OH?). [1][2][3][4] Spermatozoa are particularly susceptible to damage by processes involving free radicals for several reasons. The sperm membrane is rich in polyunsaturated fatty acids, which provide a sufficient fluidity of the sperm membrane to allow it to participate in the membrane fusion events that characterize fertilisation.…”
Section: Introductionmentioning
confidence: 99%
“…Another way to look at this problem is to address if, and how, sperm are capable of confessing their errors/flaws externally, 41 which may allow non-invasive sperm selection, e.g., in response to DNA damage 42 . However, it remains to be seen whether such biomarkers do exist or if the heterogeneity of spermatozoa is too great for such selection methods to be applicable to every patient.…”
Section: Sperm Function Testing and Icsimentioning
confidence: 99%